2017
DOI: 10.1016/j.anbehav.2016.11.025
|View full text |Cite
|
Sign up to set email alerts
|

Queen personality type predicts nest-guarding behaviour, colony size and the subsequent collective aggressiveness of the colony

Abstract: 25The founding individuals of a new group or lineage are uniquely poised to have long-lasting 26 effects on their descendants. Here we explore how the behavioural traits of new 27 foundresses influence their task allocation strategies and the downstream collective 28 behaviour of their colonies. We collected individual paper wasp (Polistes metricus) queens 29 from the wild, and measured their boldness, aggressiveness, exploration, activity, and time 30 budgets in the laboratory. We then provided queens with fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(10 citation statements)
references
References 45 publications
0
10
0
Order By: Relevance
“…The situation is, however, noticeably different for smaller colonies. Social insect queens in smaller societies can, in fact, influence colony behavior in numerous ways, including changing the course of collective decision-making (Doering and Pratt 2016), impeding disease transmission (Keiser et al 2018), physically punishing reproducing workers (Smith et al 2012), and determining collective personality traits (Wright et al 2017). In Polistes fuscatus wasps and primitively eusocial bees, queens can actually serve as activity pacemakers; their absence can disrupt normal colony rhythms (Breed and Gamboa 1977;Reeve and Gamboa 1983).…”
Section: Introductionmentioning
confidence: 99%
“…The situation is, however, noticeably different for smaller colonies. Social insect queens in smaller societies can, in fact, influence colony behavior in numerous ways, including changing the course of collective decision-making (Doering and Pratt 2016), impeding disease transmission (Keiser et al 2018), physically punishing reproducing workers (Smith et al 2012), and determining collective personality traits (Wright et al 2017). In Polistes fuscatus wasps and primitively eusocial bees, queens can actually serve as activity pacemakers; their absence can disrupt normal colony rhythms (Breed and Gamboa 1977;Reeve and Gamboa 1983).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent individual differences in behavior that impact collective outcomes, like those seen in S. dumicola , have been discovered in countless animal species such as spiders (Johnson and Sih 2005), water striders (Sih et al 1990), ants (Modlmeier et al 2012), bees (Wray et al 2011), wasps (Wright et al 2016b; Wright et al 2017), fish (Bell and Sih 2007), rodents (Daly et al 1992), birds (Aplin et al 2014), primates (Flack et al 2006), and more. For many animals, such variation has proven to be of great ecological importance (Sih et al 2004; Sih et al 2012; Jandt et al 2013; Modlmeier et al 2015).…”
Section: Discussionmentioning
confidence: 63%
“…Most studies on predator-prey interactions are performed on species of solitary or gregarious animals (Castellanos and Barbosa 2006; Bell and Sih 2007; Clinchy et al 2013; Cote et al 2013; David et al 2014). However, personality studies investigating social taxa have revealed the presence of stable differences in behavior at both the individual and group level (Jandt et al 2013; Bengston and Jandt 2014; Wright et al 2016b). The extent to which behavioral variation at either or both of these levels influences predator-prey interactions, or any other kind of species interaction for that matter, has been little explored.…”
Section: Introductionmentioning
confidence: 99%
“…However, we recovered no evidence for such an association here. This is despite the fact that queen boldness is known to shape the collective aggressiveness of workers in P. metricus (Wright, Skinker, Izzo, Tibbetts & Pruitt, 2017). Thus, at least for now, we do have support for a pace-of-life syndrome in these species.…”
Section: Discussionmentioning
confidence: 99%
“…The first of these are behavioral differences among founding queens in solitary founding species (Wright, Hyland, Izzo, McDermott, Tibbetts & Pruitt, 2018). This is because the initial work and investment of a singleton foundress (e.g., colony establishment, brood care, defence) can strongly influence in a colony’s development, behavior, and functioning (e.g., Wright et al 2017). This is true of highly eusocial species as well (Fewell & Page, 1999; Shaffer, Sasaki, Haney, Janssen, Pratt & Fewell, 2016), but we predict such effects will diminish as colonies grow and develop in highly eusocial species.…”
Section: Introductionmentioning
confidence: 99%